Foundations of applied research in the holy Qur’ān: the divine motivation in research and social change - Islam, Md Sirajul; Samsudin, Sofiah; Fadzil, Ammar (IIUM Press, 2024)
This research addresses the concept, objectives, methods, and the Qur’anic basis of applied research and the role of this form of research in achieving social change. Cause and effect are shown in how the growing world population is reducing the lands for cultivation. Subsequently, food shortages impact on social ecosystem, social justice, and social change causing a major social problem. Applied research plays a vital role to cope with such problems and challenges. Applied research is used to find solutions to common problems. This research finds that the Holy Qur’ān does not mention applied research; yet there is a basis of applied research in it. The research shows the application of the Qur’anic motivation in applied research in order to social change through increasing agricultural commodities. It provides examples of the role of applied research in the field of agriculture in the United States of America, Bangladesh, and Malaysia to generate agricultural products. In addition, to demonstrate the application of basic, scientific, and applied research through a multi-disciplinary approach, the researchers describe how a team of scientists is currently working on the ambitious project in order to transform rice from a C3 plant into a C4 plant. This research is based on reviewing library resources. The researcher used three methodologies: inductive, qualitative, and analytical approaches.